Control of regulatory T cell differentiation by the transcription factors Thpok and LRF - Carpenter, Andrea C.; Gaida, Matthias (The journal of immunology, 2017)
The CD4+ lineage-specific transcription factor Thpok is required for intrathymic CD4+ T cell differentiation and, together with its homolog LRF, supports CD4+ T cell helper effector responses. However, it is not known whether these factors are needed for the regulatory T cell (Treg) arm of MHC class II responses. In this study, by inactivating in mice the genes encoding both factors in differentiated Tregs, we show that Thpok and LRF are redundantly required to maintain the size and functions of the postthymic Treg pool. They support IL-2-mediated gene expression and the functions of the Treg-specific factor Foxp3. Accordingly, Treg-specific disruption of Thpok and Lrf causes a lethal inflammatory syndrome similar to that resulting from Treg deficiency. Unlike in conventional T cells, Thpok and LRF functions in Tregs are not mediated by their repression of the transcription factor Runx3. Additionally, we found that Thpok is needed for the differentiation of thymic Treg precursors, an observation in line with the fact that Foxp3+ Tregs are CD4+ cells. Thus, a common Thpok-LRF node supports both helper and regulatory arms of MHC class II responses.